Perioperative outcomes of upper lobectomy according to preservation or division of the inferior pulmonary ligament - Seok, Yangki; Yi, Eunjue; Cho, Sukki; Jheon, Sanghoon; Kim, Kwhanmien (Journal of Thoracic Disease, 2015)
Background: The aim of this study was to investigate the relationship between inferior pulmonary ligament division and postoperative complications. Methods: Medical records of 72 non-small cell lung cancer (NSCLC) patients who underwent video-assisted thoracic surgery (VATS) upper lobectomy between March 2012 and November 2013 performed by a single thoracic surgeon at our center were reviewed retrospectively. Patients were categorized into two groups: the division group, who underwent division of the inferior pulmonary ligament, and the preservation group, who did not. The division group included 43 patients (27 right, 16 left), while the preservation group included 29 (11 right, 18 left). Postoperative outcomes such as the presence of pleural effusion, chest tube duration, and changes in the angle and diameter of remnant bronchus were compared; bronchial diameter and angle were measured on three-dimensional (3D) reconstruction chest CT images. Results: Chest tube duration, duration of chest tube drainage >200 mL, and the presence of pleural effusion on chest X-rays taken 1 month after surgery were not significantly different between the two groups (P=0.07, 0.33, and 1.00, respectively). There were also no significant differences between groups in the presence of apical dead space or in change in bronchial angle (P=0.22 and 0.74, respectively). In 3D reconstruction images, changes in the diameter of the right middle, right lower, and left lower lobar (LLL) bronchi were similar between groups (P=0.72, 0.12 and 0.29, respectively). Change in the angle between the right bronchus intermedius (RBI) and the right middle lobar (RML) bronchus and between the RBI and the right lower lobar (RLL) bronchus were significantly different between the division and preservation groups (P=0.02 and 0.05, respectively). Conclusions: Inferior pulmonary ligament division had no clear benefits. Complications related to excessive dislocation of remnant bronchi might be associated with inferior pulmonary ligament division, but further research is needed to elucidate this relationship.